Beware of failure of early pregnancy induction – An incidental discovery of an undiagnosed bicornuate uterus at laparotomy - Rajasri G Yaliwal; Aruna M. Biradar; Laxmi Sangolli; Rakshitha Raghavendra (BLDE University Journal of Health Sciences)
A bicornuate uterus is a term used to denote a set of congenital Mullerian anomalies that are a result of incomplete fusion of the uterovaginal horns during the development of the female genital tract at the level of the fundus. A case of a woman in her late 20s with 17 weeks 2 days period of gestation is described who presented to the OBGYN outpatient department wishing to discontinue her current pregnancy. Medical termination of pregnancy (MTP) was attempted with pharmacological and mechanical methods, which all proved unsuccessful. On the last resort to open the abdomen, an incidental discovery of a bicornuate uterus was made. The pregnancy located in the left horn was removed, while the right horn was intact. Most Mullerian anomalies go unnoticed, even on ultrasound, until women give a history of recurrent pregnancy losses, preterm deliveries, or, as in the above case, failure of MTP. Increased awareness and familiarity with the diagnosis are required for active intervention in these adverse conditions.